Book reviews: "Boris Zacharowitsch Wulich, Geometrie der Kegel in normierten Räumen", (Herausgegeben von Martin R. Weber) De Gruyter Studium, De Gruyter Berlin, 2017, xvi+223 p., ISBN: 978-3-11-047884-6/pbk; 978-3-11-047888-4/ebook - COBZAȘ, S. (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
Boris Zakharovich Vulikh (1913-1978) was a distinguished Russian mathemati- cian with outstanding contributions to various domains of functional analysis, mainly to the theory of ordered vector spaces. For almost thirty years he was the head of Chairs of Mathematical Analysis at Leningrad Higher Educational Institutions, from 1957 to 1963 at the Leningrad A.I. Herzen Pedagogical Institute (now A.I. Herzen State Pedagogical University of Russia, Sankt Peterburg) and from 1963 to 1978 at the Mathematics and Mechanics Faculty of the Leningrad State University (now Sankt Peterburg State University).